OFFSET
0,3
FORMULA
Let A = g.f. A(x), then A satisfies:
A = Sum_{n>=0} x^n*A^(2n)*Product_{k=1..n} (1-x*A^(6k-4))/(1-x*A^(6k-1)) due to a q-series identity.
G.f. A(x) satisfies: A(x) = B(x*A(x)) and A(x/B(x)) = B(x) where B(x) = g.f. of A177340.
EXAMPLE
G.f.: A(x) = 1 + x + 3*x^2 + 15*x^3 + 94*x^4 + 670*x^5 + 5199*x^6 +...
A(x) = 1 + x*A(x)^2 + x^2*A(x)^7 + x^3*A(x)^15 + x^4*A(x)^26 +...
PROG
(PARI) {a(n)=local(A=1+x+x*O(x^n)); for(k=1, n, A=1+sum(j=1, n, x^j*A^(j*(3*j+1)/2)+x*O(x^n))); polcoeff(A, n)}
CROSSREFS
KEYWORD
nonn
AUTHOR
Paul D. Hanna, May 06 2010
STATUS
approved